Editorial: Current Analytical Trends in Drug Testing in Clinical and Forensic Toxicology - Gallardo, Eugenia; Barroso, Mário; Concheiro-Guisan, Marta; de-Castro-Ríos, Ana (Frontiers Media S.A., 2021)
Editorial on the Research Topic: Current Analytical Trends in Drug Testing in Clinical and Forensic Toxicology The articles included in this collection cover novel analytical approaches, including chromatographic and spectrometric methods, and sample preparation techniques for the investigation and analysis of several classes of compounds. These compounds include novel psychoactive substances (NPS) as well as other drugs and substances within the scope of clinical and forensic toxicology, and other fields, such as doping control. Current trends in bioanalysis require the constant development of novel analytical tools, which includes efficient sample collection procedures and adequate sample preparation protocols in order to maximize compound detection, even at trace levels. Taking into account that the number of substances possibly present in a sample are increasing, efficient multi-analyte methods are usually necessary.
Keywords: drugs of abuse; chromatographic techniques; clinical and forensic toxicology; new psychoactive substance; novel analytical approaches; new psychoactive substance; drug testing; trends in bioanalysis